Dietary exposure to aflatoxins in the Portuguese population – the use of biomonitoring data to assess the associated burden - Martins, Carla (2021)
Background: Human biomonitoring (HBM) is an important tool to assess the human exposure to chemicals, contributing to describe trends of exposure over time and to identify population groups that could be under risk. Aflatoxins (AFTs) are genotoxic and carcinogenic compounds causing hepatocellular carcinoma (HCC), the third leading cause of cancer deaths worldwide. In Portugal, scarce data are available regarding exposure to AFTs and none previous study used HBM data to characterize comprehensively the associated burden. Methods: 24h-urine samples (n=94) were analyzed by liquid chromatography–mass spectrometry (LC-MS/MS) for the determination of AFTs (B1, B2, G1, G2, M1). Regarding left-censored data (< LOD) a substitution approach was considered (< LOD = 0). Deterministic and probabilistic models were developed to estimate the health impact of the exposure to aflatoxins, estimating the DALYs attributed to AFTs exposure for the Portuguese population (10291k). Results: AFTs were detected in 13% (AFB1), 16% (AFB2), 1% (AFG1), 2% (AFG2) and 19% (AFM1) of the 24h-urine samples. The mean probable daily intake estimated was 16.7 and 13.4 ng/kg body weight/day, calculated mean DALYs/100k were 1.7 (0-10.7) and 1.68 (0.04-6.23) considering the deterministic and probabilistic models, respectively. Conclusion: The present study generated, for the first time and within a HBM study, reliable and crucial data to characterize the burden associated to Portuguese population exposure to aflatoxins. The obtained results constitute an important contribution to support risk managers in the establishment of preventive policy measures that contribute to ensure the public health protection.